Legal Analysis of Fraud Disputes in Franchise Practices: An Overview of the Perspective of Civil Society Capita Selecta - Ika Rachmawati Sukarno Putri (CV. Rayyan Dwi Bharata, 2023)
This article discusses a legal analysis of fraudulent disputes that occur in franchise practices. The main focus of this analysis is to look at fraud disputes in franchise practices from the perspective of civil society capita selekta. This research was conducted by collecting data from relevant primary and secondary legal sources. In the context of franchising, fraud disputes occur when a franchisor knowingly commits fraud or provides false information to a franchisee with the aim of making a profit. This kind of fraud often involves misunderstanding of the franchise contract, injustice in business practices, lack of communication and support from the franchisor, and non-compliance with operational standards. This legal analysis of fraudulent disputes in franchise practices uses the principles of contract law, fairness and protection of rights. Contract law principles are used to interpret, enforce and enforce franchise contracts. The principle of justice ensures that dispute resolution is carried out in a fair and objective manner. Meanwhile, protection of rights is important in maintaining the integrity of the franchise industry and promoting the sustainability of this industry. In handling fraud disputes in franchising practices, it is important for franchisees to understand the franchise contract well and comply with the stipulated conditions. In the event of fraud on the part of the franchisor, the franchisee may bring legal claims based on breach of contract, unfair business practices or fraud. In conclusion, the application of legal principles in handling fraud disputes in franchise practices is very important. This article provides an overview from the perspective of civil society, taking into account the principles of contract law, justice and protection of rights. This research provides a better understanding of fraud disputes in franchise practices and their relevance in the context of civil law capita selekta.